Assessment of noise pollution level in a tertiary care hospital of Imphal, Manipur - Laishram, Jalina; Sonarjit Singh, Khangembam; Syiem, Tyllibor; Akoijam, Brogen Singh (International Journal Of Community Medicine And Public Health, 2023)
Background: Noise pollution is a major public health problem. Previous studies reported the presence of noise pollution in various hospital settings around the world. There are few studies conducted on noise pollution in the north eastern part of India especially in Manipur. Therefore, the study was undertaken to assess noise pollution in a tertiary hospital of Manipur for future suggestive measures to reduce noise and associated health impacts. Methods: An observational study was conducted in a public tertiary care hospital of Imphal, Manipur. Data collection for noise level measurement was done by using a digital sound level meter instrument and mobile sound meter app. The data was analyzed using IBM SPSS for Windows, version 21.0. Armonk, NY. Results: The highest sound level of 87.6 dB(A) was recorded in the general OPD counter. Among the OPDs, Medicine OPD recorded the highest sound level of 85.2 dB(A). Parking areas recorded an average maximum of 80.5 dB(A). Hospital wards recorded an average maximum sound of 77.4 dB(A). Conclusions: In this study, the maximum sound level in a week average was found in parking areas of the hospital. Majority of the places around the hospital recorded a noise level which is beyond the recommended CPCB noise level 2000.